Pemberdayaan Masyarakat Melalui Pembangunan Wisata Parsariran Kecamatan Batang Toru - Silviana Batubara; Wisnu Yusditara; Makhrani Makhrani (Jurnal Pengabdian Kepada Masyarakat, 2024)
Parsariran nature tourism is located in Batang Toru District, South Tapanuli Regency, which is one of the famous tourist destinations. This project aims to discuss the sustainability of the community empowerment process carried out with the development of tourist villages including forms of community empowerment and the results of community empowerment carried out. The approach to this aproject uses qualitative methods to discuss community characteristics and tourism potential. Data collection in this project was obtained through interviews and observation. The results of observations stated that there were many factors that made Parsariran Tourism in the Batang Toru sub-district a tourist destination with a high number of enthusiasts, including cool air, lots of hot springs, high community productivity and a fairly high rainfall factor which made the potential for hydropower development. Forms of community empowerment involve the role of the community from planning to implementing activities. The programs that have been carried out are in the form of socialization and training which includes socialization on tourism marketing strategies, socialization on tourism safety, socialization on tourism management systems and training on recycle or recycling of waste. Empowerment of the community through the development of tourist villages has implications for improving the quality of tourism and managing nature tourism in a more sustainable tourism area.